Rituximab with cyclophosphamide, vincristine, non-pegylated liposomal doxorubicin and prednisone as first-line treatment for splenic marginal zone lymphoma: a Fondazione Italiana Linfomi phase II study. Issue 12 (2nd December 2015) - Iannitto, Emilio; Luminari, Stefano; Tripodo, Claudio; Mancuso, Salvatrice; Cesaretti, Marina; Marcheselli, Luigi; Merli, Francesco; Stelitano, Caterina; Carella, Angelo Michele; Fragasso, Alberto; Montechiarello, Elisa; Ricciuti, Giuseppina; et al.
Abstract : Rituximab ® provides high response rates and effective disease palliation in patients with splenic marginal zone lymphoma (SMZL). We conducted a phase II trial in patients with SMZL who were either untreated or were splenectomized but had shown disease progression within 1 year after splenectomy. Treatment consisted of six courses of Rituximab with cyclophosphamide, vincristine, non-pegylated liposomal doxorubicin and prednisone (R-COMP). Fifty-one patients were eligible for the analysis. The overall response rate was 84%. The 6-year progression-free survival and overall survival were 54% and 72%, respectively. Toxicity was substantial (grade ≥ 3 neutropenia: 26%; grade ≥ 3 infections: 8%). Of the 15 deaths, two occurred on treatment (one sepsis and one pneumonia). Six deaths were due to lymphoma progression, four to secondary neoplasia, one to sepsis, one to pneumonia and one to splenectomy complications. R-COMP should be restricted to patients with bulky disease associated with symptoms or to patients with possible histological transformation.